Last chance in Hong Kong? Obstacles on the road to the conclusion of the Doha Round - Heribert Dieter (Stiftung Wissenschaft und Politik (SWP), 2005)
The World Trade Organization, the WTO, was established more than 10 years ago and at first glance the utility of this multilateral organization is beyond question. Since 1996 it has added 35 new member states and an additional 30 countries are preparing for membership. At the same time, however, the WTO is facing enormous challenges. A descent into meaninglessness can in no way be ruled out. The WTO Ministerial Conference, which takes place from December 13-18, 2005 in Hong Kong, will send an important signal in this context. The policies of the two most significant actors in the WTO, the EU and the U.S., will be decisive. Because of the inability of these two actors to cooperatively solve their serious bilateral disputes, such as the Airbus/Boeing subsidy dispute, the WTO is navigating through rough seas. The situation is made even more critical by the fact that the Fast Track Authority of the American government expires in 2007. If this is not extended, which as of today seems likely, the American Congress would have the right to discuss trade agreements in detail and demand changes. This could result in a deadlock on trade issues within the American government, which would in turn paralyze the entire WTO. (SWP-Comments / SWP)
Keywords: 320